Drought Priming at Vegetative Growth Stage Enhances Nitrogen‐Use Efficiency Under Post‐Anthesis Drought and Heat Stress in Wheat. (17th October 2016) - Liu, S.; Li, X.; Larsen, D. H.; Zhu, X.; Song, F.; Liu, F.
Abstract: To study the effects of early drought priming at 5th‐leaf stage on grain yield and nitrogen‐use efficiency in wheat ( Triticum aestivum L.) under post‐anthesis drought and heat stress, wheat plants were first exposed to moderate drought stress (drought priming; that is, the leaf water potential reached ca. −0.9 MPa) at the 5th‐leaf stage for 11 days, and leaf water relations and gas exchange rates, grain yield and yield components, and agronomic nitrogen‐use efficiency (ANUE) of the primed and non‐primed plants under post‐anthesis drought and heat stress were investigated. Compared with the non‐primed plants, the drought‐primed plants possessed higher leaf water potential and chlorophyll content, and consequently a higher photosynthetic rate during post‐anthesis drought and heat stress. Drought priming also resulted in higher grain yield and ANUE in wheat under post‐anthesis drought and heat stress. Drought priming at vegetative stage improves carbon assimilation and ANUE under post‐anthesis drought and heat stress and their combination in wheat, which might be used as a field management tool to enhance stress tolerance of wheat crops to multiple abiotic stresses in a future drier and warmer climate.